Synthesis of new alkyl derivatives of N(1)-(2'-bromo-1',1'-difluoro-2'-chloroethyl)uracil with potential antitumor activity - O. V. Velchynska (Zaporozhye State Medical University, 2020)
The most common ways of their chemical modification are used namely, electrophilic and nucleophilic substitution reactions during the purposeful search for active substances among pyrimidines with aromatic properties. Antimetabolites of pyrimidine metabolism are one of the objects of the most successful and promising areas of search for highly effective antitumor drugs. The aim of the work was the purposeful search for biologically active substances by carrying out alkylation reactions on the heterocyclic nucleus. Materials and methods. Methods of organic synthesis, physical and instrumental methods of analysis of organic compounds (NMR-spectroscopy 1Н, gas-liquid chromatography with UV-detection, IR-spectrometry, elemental analysis). Results. Objects of the study were new alkyl derivatives of N(1)-(2'-bromo-1',1'-difluoro-2'-chloroethyl)uracil which synthesized on the basis of N(1)-(2'-bromo-1',1'-difluoro-2'-chloroethyl)uracil and alkylating agents of different chemical structure: methyl iodide, dimethyl sulfate in alkaline medium, ethylene, acetylene, ethylene oxide. In the course of this work, we investigated the range of chemical properties of the synthesized substances on the example of N(1)-(2'-bromo-1',1'-difluoro-2'-chloroethyl)uracil (I), in particular the ability to engage in a variety of substitution reactions, namely, alkylation reactions across a heterocyclic nucleus to produce new biologically active derivatives. As a result of the transformations, a number of derivatives were obtained - compounds II-V. Thus, alkylation with methyl iodide or dimethyl sulfate in an alkaline medium led to the formation of carbon atom С(5) substitution products (Compound II). The reactions of alkylation with ethylene (compound III), acetylene (compound IV), and ethylene oxide (compound V) were similar. It had previously been established that the structural analogs of the synthesized compounds can be successfully used to create molecular mixtures with bacterial lectins 102 and 668 as the most active producents of extracellular lectins. For example, the bis-derivative of N(1)-(2'-bromo-1',1'-difluoro-2'-chloroethyl)uracil (I) as part of a molecular mixture with bacterial lectin 102, which was the inactive component on lymphosarcoma Plissa, exhibits antitumor effect of up to 48.0 % on the specified tumor strain. It was found that when replacing of lectin's component at the molecular mixture, namely, lectin 102 on lectin 668, for lymphosarcoma Plissa registered higher % of inhibition of tumor growth: % of inhibition of tumor growth changed from 48.0 to 50.0 at a dose of 24.0 mg/kg (for comparison preparation 5-FU: growth inhibition of lymphosarcoma Plissa was - 55.0 %). Conclusion. Thus, synthesized derivatives of the source N(1)-(2'-bromo-1',1'-difluoro-2'-chloroethyl)uracil - compounds II-V, will allow to expand the range of objects to search for original biologically active substances from potential antitumor activity that was reasonably predicted by the presence of appropriate pharmacophores in the synthesized molecules and the positive antitumor activity in the previously synthesized structural analogues of the parent compound.